2023
DOI: 10.1039/d2dt03845e
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent chemical substitution in double–double perovskite-type ALaLiTeO6:Mn4+ (A = Ba2+, Sr2+, Ca2+) phosphors enabling wide range crystal field strength regulation and efficient far-red emission

Abstract: Mn4+-activated phosphors have shown wide perspective applications in phosphor-converted white light-emitting diodes (pc-WLEDs) and pc-LEDs used in illumination and indoor plant cultivation, respectively. Recently, double perovskites A2B′B″O6 with tunable crystal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…It is well known that deep-red emitting Mn 4+ ions favor octahedral sites and their emission wavelengths depend on the strength of the Mn 4+ -O 2− covalent bonding, that is, stronger Mn 4+ -O 2− covalent bonding usually leads to a longer emission wavelength. 54,55 Hence, the 666 nm emission should be attributed to Mn 4+ emitters residing on the larger Mg1 and Mg2 sites, whereas the 712 nm emission should be ascribed to Mn 4+ ions distributed on the smaller Sb1 and Sb2 sites.…”
Section: Electronic Structurementioning
confidence: 99%
“…It is well known that deep-red emitting Mn 4+ ions favor octahedral sites and their emission wavelengths depend on the strength of the Mn 4+ -O 2− covalent bonding, that is, stronger Mn 4+ -O 2− covalent bonding usually leads to a longer emission wavelength. 54,55 Hence, the 666 nm emission should be attributed to Mn 4+ emitters residing on the larger Mg1 and Mg2 sites, whereas the 712 nm emission should be ascribed to Mn 4+ ions distributed on the smaller Sb1 and Sb2 sites.…”
Section: Electronic Structurementioning
confidence: 99%
“…18,19 It has been reported that the substitution of Ca/Sr/Ba cations allows the improvement of the luminescence thermal stability of ALaLiWO 6 20 and ALaLiTeO 6 . 21 The main luminescence properties of Mn 4+ doped BaLaLiTeO 6 and BaLaLiWO 6 were earlier reported to be have prospects for plant cultivation technologies. 22,23 Meanwhile, a good thermal stability has been documented for Mn 4+ doped BaLaLiTeO 6 .…”
Section: Introductionmentioning
confidence: 98%
“…In particular, the double perovskite structure of ALaLiTeO 6 (A = Ca, Sr, and Ba) has received widespread attention as a matrix for luminescent materials. [28][29][30] In 2014, S. K. Sali et al for the first time synthesized a double perovskite-type compound BaA'LaTeO 6 (A′ = Na, K, and Rb) and determined its crystal structure using Rietveld analysis and neutron diffraction data. 31 In 2017, G. Subodh et al synthesized the B-site ordered double perovskite ALaLiTeO 6 (A = Ba and Sr) and investigated the vibrating phonon modes for the first time.…”
Section: Introductionmentioning
confidence: 99%